A disturbed processing of graviceptive pathways may be involved in the pathophysiology of balance disorders in patients with multiple sclerosis - Fonseca, Bruna Antinori Vignola da; Pereira, Cristiana Borges; Jorge, Frederico; Simm, Renata; Apostolos-Pereira, Samira; Callegaro, Dagoberto (Arquivos de Neuro-Psiquiatria, 2016)
The purpose of this study was to determine the relationship between perception of verticality and balance disorders in multiple sclerosis patients. We evaluated patients and healthy controls. Patients were divided into two groups according to their risk of fall, with or without risk of fall, measured by a Dynamic Gait Index scale. Graviceptive perception was assessed using the subjective visual vertical test. Patients with risk of fall showed worse perception than those without risk of fall, p < 0.001. Misperception of verticality was correlated with the dynamic gait index scores (p < 0.001), suggesting that the larger the error for verticality judgment, the greater risk for falling. Considering that the perception of verticality is essential for postural control, our results suggested that the disturbed processing of graviceptive pathways may be involved in the pathophysiology of balance disorders in these patients.
Keywords: postural balance; multiple sclerosis; vestibular function tests; gravity sensing; sensation disorders; accidental falls